The Traumatic Experience of Clinical Nurses During the COVID-19 Pandemic: Which Factors are Related to Post-Traumatic Growth? - Zhang XT; Shi SS; Ren YQ; Wang L (Dove Medical Press, 2021)
Xin Tong Zhang,* Song Song Shi,* Yu Qin Ren, Li Wang Department of Emergency, Nantong First People’s Hospital, Nantong, 226001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yu Qin RenDepartment of Emergency, Nantong First People’s Hospital, No. 6 of Haierxiang North Road, Chongchuan District, Nantong, 226001, People’s Republic of ChinaTel +86 15962956088Email renyuqindr@21cn.comObjective: Post-traumatic growth (PTG) is a positive result of fighting against traumatic events. This study aimed to investigate the current status of PTG of clinical nurses and analyze its influencing factors.Methods: A total of 1790 nurses participated in the study and completed the questionnaire. Demographic data and related scales of PTG, post-traumatic stress disorder, coping style, social support, and self-efficacy were collected online. Through univariate analysis and multiple linear regression analysis, the related influencing factors were studied.Results: The total score of PTG of 1790 nurses was 67.17 ± 14.79. The analysis revealed that good social support and self-efficacy were important factors to improve the level of PTG of clinical nurses, while bad psychological state and working for many years were the negative factors of PTG.Conclusion: Good social support and self-efficacy can help clinical nurses cope with the novel coronavirus disease 2019 pandemic and accept the disease’s challenges. If these factors can be considered in clinical practice, this will help promote clinical nurses’ mental health.Keywords: COVID-19, post-traumatic growth, psychological impact, nurse, influencing factors